Research into the Impact of Phase Shifter Failures on the Characteristics of Slotted Waveguide Array Antenna - M. R. Bibarsov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Currently, the impact of phase shifter (PS) failures on the characteristics of phased antenna arrays, slotted waveguide array antenna (SWAA) in particular, represents a significant problem. A review of publications shows that insufficient attention has been paid to PS failures.Aim. To investigate the characteristics of a SWAA in the event of PS failures, when their phase takes a value equal to zero instead of the required value.Materials and methods. The methods of statistical modeling methods were used to study the impact of failures on SWA characteristics. Calculations were carried using the Mathcad 15 software package.Results. An algorithm for statistical modeling of the impact of PS failures on SWAA characteristics is proposed. A relationship that connects the radiation pattern with the volume of the statistical sample and the number of failed PSs is given. The malfunctions of emitters from 5 to 35 out of 50 elements were studied. Changes in the following characteristics were obtained: standard deviation – from 0.064 to 0.18, radiation pattern width – from 8 to 18 %, the level of side lobes – from 13 to 59 %, radiation power – from 0.9 to 0.3.Conclusion. The results obtained can be used in radio-electronic systems with antenna arrays at the stage of their development. Future work will address PS failures with phases being established randomly and with random values, as well as the case of PS failures where power does not pass into the emitter. Another important direction concerns compensation of distortions resulting from failures of antenna elements.